PHOTOVOLTAIC POWER PLANT INSPECTION AND DIAGNOSTIC - Vrana, Michal; Moravek, Jan; Mastny, Petr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
This paper presents methods of photovoltaic panel inspection in the field. The aim is to verify value of on-site tests. The basic parameters for comparing the quality of photovoltaic panels are indicated by the manufacturer’s datasheet. Diagnostic in the field commonly uses a combination of different analyzers and infrared cameras. The paper compares the evaluation of the parameters at different climatic conditions by special photovoltaic analyzer, conventional analyzer with recalculation according the IEC standards and flash tester. The comparison of different methods and analyzers has been performed with the practical experience from the measurements. Further, the standards for the inspection of photovoltaic panels and best practices for their implementation are described.